The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.5204/mcj.2214
|View full text |Cite
|
Sign up to set email alerts
|

Post-Logo

Abstract: Spurred by global institutions and treaties such as the General Agreement on Tariffs and Trade (GATT) and its’ bantling the World Trade Organisation (WTO), the past three decades have seen many nations of the world develop an economic interconnectedness that parallels the great free trade movement of the late Nineteenth and early Twentieth Centuries. Free trade and the resultant economic ‘globalisation’ have had mixed results for many countries and groups within countries and has incited a complex, ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…1,1-Diamino-2,2-dinitroethene (DADNE or FOX-7) is one of the most promising insensitive HE crystals, with performance comparable to cyclotrimethylenetrinitramine (RDX). FOX-7 has a relatively simple molecular structure, and its molecular and crystalline characteristics are similar to those of other known IHE crystals, including triaminotrinitrobenzene (TATB). , Thus, FOX-7 is an attractive prototype IHE crystal. Since its synthesis in 1998, considerable experimental efforts have been made to understand its crystal structures at extreme pressures and temperatures. It was reported that the ambient structure of FOX-7, α phase (monoclinic, P 2 1 / n ), can transform to three HT (β, γ, and δ) and two HP (α′ and ε) phases.…”
Section: Introductionmentioning
confidence: 99%
“…1,1-Diamino-2,2-dinitroethene (DADNE or FOX-7) is one of the most promising insensitive HE crystals, with performance comparable to cyclotrimethylenetrinitramine (RDX). FOX-7 has a relatively simple molecular structure, and its molecular and crystalline characteristics are similar to those of other known IHE crystals, including triaminotrinitrobenzene (TATB). , Thus, FOX-7 is an attractive prototype IHE crystal. Since its synthesis in 1998, considerable experimental efforts have been made to understand its crystal structures at extreme pressures and temperatures. It was reported that the ambient structure of FOX-7, α phase (monoclinic, P 2 1 / n ), can transform to three HT (β, γ, and δ) and two HP (α′ and ε) phases.…”
Section: Introductionmentioning
confidence: 99%
“…In July 1912 and 1913, Labour agents like House and ILP movement activists serving on the executive and sharing the gala platform exchanged barely disguised insults (Mates, 2016a: 195, 207-10, 273-4). The second disunity evident after 1911 was the generational cleavage within Labour between the former Liberal House (born 1854) and the leading figures of a younger ILP generation: Jack Lawson (born 1881) and W. P. Richardson (born 1873) (Bellamy and Martin, 1974). Between them were ILP activists like Jos Batey (born 1867), still House's junior by thirteen years.…”
Section: Leaders V Led ('Rank-and-file'): the Historiographical Debatesmentioning
confidence: 99%
“…Indeed, there is even a hitherto unrecognised 'disunity' in terms of Lawson's own political career, between his early militancy and later moderate labourism. The main interpretations of Lawson have suggested his later politics characterised his ideology from the outset, when the reality is far more complex and interesting, revealing a complex and fully three-dimensional activist (Bellamy and Martin, 1974;Bythell, 2016).…”
Section: Leaders V Led ('Rank-and-file'): the Historiographical Debatesmentioning
confidence: 99%
“…Thermal decomposition of solid FOX-7 above 500 K produces carbon monoxide (CO), carbon dioxide (CO 2 ), ammonia (NH 3 ), hydrogen cyanide (HCN), cyanic acid (HOCN), isocyanic acid (HNCO), formic acid (HCOOH), water (H 2 O), nitric oxide (NO), nitrogen dioxide (NO 2 ), nitrous acid (HONO), nitrous oxide (N 2 O), and dinitrogen trioxide (N 2 O 3 ). , In such cases, hydroxyl radicals (OH) and NO 2 were found to abstract hydrogen to generate H 2 O and HONO . At elevated temperatures, α-FOX-7 transitions to a β-phase above 385 K and eventually to γ- and δ-FOX-7 before thermally decomposing. ,, , Recently, ε- and ζ-phases have also been synthesized that convert to a γ-phase upon heating . Although subtle changes were observed in the infrared spectrum upon cooling to cryogenic temperatures under vacuum, a distinct low-temperature phase has not been observed .…”
Section: Introductionmentioning
confidence: 99%